Comunicação organizacional e economia criativa: um olhar sobre o Complexo Cultural da Marinha do Brasil no Rio de Janeiro - Moulin, Lorena Fraga Costa (2021)
This exploratory research aims to identify how the Cultural Complex of the Brazilian Navy, an equipment circuit that includes museums, tours, exhibition areas and historical pieces, in the city center of Rio de Janeiro, uses Organizational Communication to promote the Creative Economy in the region. Even though these cultural facilities had been in operation since the middle of the 20th century, after the restructuring works of the city's port region, undertaken in connection with the 2016 Olympics, the cultural options of the Navy were more visible to the population. The work relates the elements of the Creative Economy "culture", "heritage", "development" and "creative territory" with the cultural equipment of the Navy. In addition, the study also integrates this approach with the concepts of Organizational Communication and Public Communication. Through bibliographic and documentary research, semi-open in-depth interviews, with technical content analysis procedure, it is concluded that the cultural activities of MB in the Cultural Corridor of RJ stimulate the development of the Creative Economy in the region; MB's cultural assets in the Cultural Corridor of RJ reinforce positive aspects of the Brazilian Navy reputation in the country; and the Complex's cultural facilities are public communication tools. It was also concluded that the Navy´s organizational memory projects can be operationalized as a communication strategy, in addition to identifying the heritage as Public Communication. Research has shown that the Complex assists in the maintenance of citizens in that region, through its cultural facilities. It is also observed that the Cultural Complex of the Navy preserves, values and disseminates the historical heritage of both the Armed Forces and Brazil, a stimulus provided to the Creative Economy in the city of Rio de Janeiro, and, consequently, to the development of the region